2017
DOI: 10.1093/ofid/ofx095
|View full text |Cite
|
Sign up to set email alerts
|

Financial Incentives for Adherence to Hepatitis C Virus Clinical Care and Treatment: A Randomized Trial of Two Strategies

Abstract: Background.Although rates of sustained virologic response (SVR) after hepatitis C virus (HCV) treatment with direct-acting antivirals (DAAs) surpass 90% in trials and some more “real world” settings, some patients, such as those with substance use disorders, will be challenged to adhere to HCV care.Methods.To assess the feasibility of 2 strategies for financially incentivizing adherence to HCV care, patients with a substance use history prescribed 12 weeks of a sofosbuvir-containing regimen were randomized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
(29 reference statements)
2
9
0
Order By: Relevance
“…Anecdotally, since the data lock that preceded this analysis, 9/13 LTFU individuals have been re-engaged in care, producing a residual LTFU rate of 2% (n/N = 4/229). This suggests that a multidisciplinary approach to managing social, psychiatric, medical, and addiction-related needs could be a highly relevant strategy to engage patients in care and re-engage those who were LTFU [ 25 ]. In fact, the use of multidisciplinary systems is key to addressing addiction-related needs, as treatment o f PWID in nonmultidisciplinary settings is not recommended given the diversity of their needs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotally, since the data lock that preceded this analysis, 9/13 LTFU individuals have been re-engaged in care, producing a residual LTFU rate of 2% (n/N = 4/229). This suggests that a multidisciplinary approach to managing social, psychiatric, medical, and addiction-related needs could be a highly relevant strategy to engage patients in care and re-engage those who were LTFU [ 25 ]. In fact, the use of multidisciplinary systems is key to addressing addiction-related needs, as treatment o f PWID in nonmultidisciplinary settings is not recommended given the diversity of their needs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These medications have sustained virologic response (SVR) rates as high as 97% in clinical trials, compared to approximately 50% with interferon-based regimens [ 12 ]. SVR is associated with decreased morbidity and mortality, and improved quality of life [ 13 ]. Despite these tangible benefits, insufficient research has been done on real-world treatment outcomes in uninsured HCV infected patients treated with DAAs, and even less in indigent patient populations [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants reported that financial incentives may prove particularly useful in promoting uptake of HCV rapid testing and education in the shelter setting. Financial incentives may serve as a useful tool for engaging at risk people in HCV testing [32], such as homeless adults. As many participants had prior experience with HCV rapid testing, scaling up HCV prevention services so that they become a routine part of the intake process could be one way to ensure that those at highest risk of infection and transmission are tested and linked to care.…”
Section: Discussionmentioning
confidence: 99%